The Imaginary Line Across Yogyakarta Land as an Ethnomathemathics Study - Febriani Febriani; Aditia Pramudia Sunandar; Ulfa Aulia Syamsuri; Wipsar Sunu Brams Dwandaru (Universitas negeri Yogyakarta, 2023)
In attempt to explore Yogyakarta, the heritage city of Indonesia, the well known landmark, Tugu Pal Putih and the Yogyakarta Imaginary Line is explored. The purpose of this paper is to describe that this cultural context may be used as a reference for geometry learning. The method used in this research is a descriptive qualitative involving two historian experts in interviews. The results are that this line can be explored through ethnomathematics studies based on points, straight lines, comparison of distances between points on the imaginary line and the extension of the imaginary line. This line can be illustrated by an imaginary point located at the Tugu Pal Putih as the starting point to focus on thinking of the mathematical object. This line not only divides Yogyakarta imaginatively but also according to natural boundaries such as rivers. The extension of the imaginary line forms an area called the fertility area. The description of the patterns formed on the Yogyakarta Imaginary Line through ethnomathematics is expected to be used further as materials in the mathematics learning process.